2016
DOI: 10.1179/1973947815y.0000000039
|View full text |Cite
|
Sign up to set email alerts
|

Is sunitinib-induced hypothyroidism a predictive clinical marker for better response in metastatic renal cell carcinoma patients?

Abstract: The occurrence of hypothyroidism during treatment in patients was significantly associated with longer PFS, OS and better ORR in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A lot of predictive factors that were associated with worse ORR, shorter PFS or OS have been shown in previous retrospective studies (Table ) . Several studies have focused targeted molecules and their related factors in tumor tissues or serum, such as VEGFRs and tuberous sclerosis complex .…”
Section: Prognostic Factors For Mrcc Patients Treated With Targeted Tmentioning
confidence: 99%
See 3 more Smart Citations
“…A lot of predictive factors that were associated with worse ORR, shorter PFS or OS have been shown in previous retrospective studies (Table ) . Several studies have focused targeted molecules and their related factors in tumor tissues or serum, such as VEGFRs and tuberous sclerosis complex .…”
Section: Prognostic Factors For Mrcc Patients Treated With Targeted Tmentioning
confidence: 99%
“…Several studies showed that some AEs, such as hypertension or hand‐foot syndrome, were correlated with the efficacy of targeted agents . These AEs are defined as “on‐target AEs” and others are defined as “off‐target AEs.” On‐target AEs should be managed in order to continue targeted therapy, whereas management including stopping or changing agents is considered for off‐target AEs …”
Section: Prognostic Factors For Mrcc Patients Treated With Targeted Tmentioning
confidence: 99%
See 2 more Smart Citations
“…SUN-induced hypothyroidism has also been proposed as a possible predictive factor for the outcome of the cancer treatment, although the conclusions are still unclear [23][24][25][26][27]35,36]. A preliminary study of SUN treatment for mRCC suggested that hypothyroid patients had a significantly longer PFS than euthyroid patients [22].…”
Section: Hypothyroidism and Cancer's Outcomementioning
confidence: 99%